Effect of the Heat treatment on Mechanical and Physical Properties of Direct Recycled Aluminium Alloy (AA6061) - Hussein Rady, Mohammed; Mustapa, Mohammad Sukri; Wagiman, Abdullah; Al-Alimi, Sami; Shamsudin, Shazarel; Lajis, Mohd Amri; Mansor, Mohamad Norani; Harimon, Mohd Azhar (International Journal of Integrated Engineering, 2020)
Products by solid-state recycling of aluminum chips in hot extrusion process were controlled by temperature related parameters using preheating temperature 450 °C, 500 °C, and 550°C for 1 hr, 2 hr, and 3 hr preheating time. By using Design of Experiments (DOE), the results found that the preheating temperature is more important to be controlled rather than the preheating time in analysis both mechanical and physical properties. The results also found that increasing of temperature led to the high tensile strength and low microhardness. The profile extruded at 550 °C with 3 hr duration had gained the optimum case to get the maximum tensile strength and the profile extruded at 450 °C with 1 hr had result the optimum case to gain the maximum microhardness. For the optimum cases, heat treatment was carried out using quenching temperature at 530 ºC for 2 hr and aging process at 175 ºC for 4 hr. The tensile strength and microhardness of extrudes specimens were improved significantly by heat treatment.